Turners - Gregory, Noel (Ready to paint the masters, 2010)
No other books on the market offer the opportunity to reproduce the Master's work without the need for great drawing skill. The step-by-step demonstrations explain in great detail how to copy Noel Gregory's expert painting style, so that even beginners will have the confidence to have a go